Re-Aktivasi Instagram Sebagai Pemasaran Digital: Studi Kasus Psikologi Pemasaran UMKM BM - Asiadhy, Zidan Rasyid; Aulia, Khasyina; Millennia, Aisyah Vivie; Indraswari, Candra (Universitas Islam Negeri Raden Intan Lampung, 2022)
Covid-19 is still endemic in all countries of the world and affects all sectors of people's lives, including Indonesia. In Indonesia, almost all sectors are affected, especially the economic ecosystem that has become the foundation of society. MSME is one of the activities that increase growth, movement, and economic development. Researchers are interested in exploring and examining the marketing methods carried out by BM SMEs. This study uses a descriptive qualitative method approach. The research informants this time were two people, the initials IS and AG. The IS informant is the owner of BM, while the AG informant is an employee of the marketing department. The data collection method used in this study was semi-structured interviews. The researcher uses a time triangulation technique which aims to cross-examine informants who know very well about BM. The results show that BM has Instagram social media but is not active. So that it is not optimal in doing marketing, especially in online marketing. Suggestions for business owners are to keep abreast of the times, such as optimizing the use of technology that is useful in developing a business. In addition, it also maintains and improves product quality so that it can compete with similar business people. Then suggestions for further researchers are to examine other factors in order to expand the scope of research.Keywords: Instagram, marketing psychology, MSME